2017 Western Atlantic Hurricane Season Maximum Wind Speed and Mangrove Damage - Paul Taillie (PANGAEA, 2020)
These data are associated with an article published in Environmental Research Letters in 2020 (currently in revision). The aim of the paper was to quantify the extent of mangrove damage resulting from the 2017 hurricane season in the Western Atlantic hurricane basin. Mangrove damage was quantified with changes in NDVI calculated from satellite imagery from the Landsat 7 and 8 satellites using Google Earth Engine. Details regarding methods and Earth Engine code can be found in the supplemental information with the manuscript.